(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The so-called Turing test-which its author, Alan Turing, coined as a game of imitation in 1950-served as a stimulus to computer scientists investigating as pioneers in artificial intelligence; some believe, diverting their true ends. But it also began a long half-century controversy over its validity. Then, abandoned by computer scientists as a historical piece. Not so for philosophers, who continue to seek a formal, scientific-philosophical proof of the mind-matter relationship, for it is a secular problem: what is human nature and if there are differences between man and everything else in the universe? The present work is an anthological chronicle of how the problem has been treated by some scientists and philosophers, from the proposal of Turing until today.